Pengaruh Rasio Utang Terhadap Hasil Pengembalian Investasi Pada PT Jamkrida Jabar - Euis Hernawati; Nur Hasanah (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2019)
This research was aimed to determine the influence of debt ratio to the return on investment at PT Jamkrida Jabar. The research method used was quantitative method, while the data collection techniques used were by observation and literature study. The data management used SPSS (statistical product and service solutions). From the research conducted, it was obtained the correlation coefficient of 0,984 indicated that there is a very strong influence of debt ratio to the return on investment (ROI) at PT Jamkrida Jabar. While the coefficient of determination is 96,8% indicated that the return on investment influenced by the debt ratio and remaining 3,2% was influenced by other factors. The Suggestion that can be given by the writer that the company expected to use their own capital to finance its assets, in order to avoid obstacles that will result in increased assets financed by debt so that the company’s revenue may increase.